Pengaruh Tingkat Pengangguran Terbuka dan Pendidikan terhadap Tingkat Kemiskinan di Kabupaten Kediri - Emelia Yesrada Sebriana; Hendry Cahyono (Universitas Negeri Surabaya, 2022)
The purpose of this research to determine the effect of the open unemployment and education on the poverty level in Kediri Regency. This was motivated by problems occurred due to the Covid-19 which resulted in an increase in the unemployment rate due to the large number of layoffs during the pandemic. The analysis technique used is multiple linear regression analysis. The results show that the open unemployment rate has a positive effect on the poverty level and education has a effect significant directly affect the poverty level of Kediri Regency. Output of the analysis is the open unemployment and education simultan positive on the a poverty level in Kediri Regency. Education has a negative effect on poverty.